1988
DOI: 10.1210/endo-123-5-2331
|View full text |Cite
|
Sign up to set email alerts
|

Rat Ovarian Renin: Characterization and Changes during the Estrous Cycle*

Abstract: To demonstrate the existence and help clarify the function of renin in the rat ovary, we have characterized rat ovarian renin and examined ovarian renin levels during different stages of the rat estrous cycle. We show that high concentrations of active renin are present in the rat ovary (2.9 ng angiotensin I/h/mg). Ovarian renin activity has a pH optimum of about 7.0 and is due to a glycosylated aspartyl protease with an apparent mol wt of 39,000. These properties of rat ovarian renin are identical to previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…3) On the other hand, renin ordinarily has a neutral optimum pH (pH 6.0-8.0), and does not show a typical bell shape in pH dependence against homologous and heterologous angiotensinogens. [4][5][6][7][8][9] The reason for this unique pH dependence has not been elucidated, although Tyr83, 10) Ser84, 11) and Ala317 12) of human renin and His9 11) of a synthetic substrate have been reported to contribute to the pH dependence of the renin-angiotensinogen reaction. The catalytic mechanism of renin is generally thought to be analogous to that of a typical aspartic proteinase, but this cannot explain the neutral optimum pH and the unique pH profile of the renin reaction.…”
Section: Asp-coomentioning
confidence: 99%
“…3) On the other hand, renin ordinarily has a neutral optimum pH (pH 6.0-8.0), and does not show a typical bell shape in pH dependence against homologous and heterologous angiotensinogens. [4][5][6][7][8][9] The reason for this unique pH dependence has not been elucidated, although Tyr83, 10) Ser84, 11) and Ala317 12) of human renin and His9 11) of a synthetic substrate have been reported to contribute to the pH dependence of the renin-angiotensinogen reaction. The catalytic mechanism of renin is generally thought to be analogous to that of a typical aspartic proteinase, but this cannot explain the neutral optimum pH and the unique pH profile of the renin reaction.…”
Section: Asp-coomentioning
confidence: 99%
“…Estrogen causes over-expression of the RAS by augmenting both tissue and circulating levels of Aogen (51,52) and renin (53)(54)(55)(56). Plasma renin activity (PRA) increases after estrogen treatment in nephrectomized rats (53).…”
Section: Estrogen Regulation Of Ras Componentsmentioning
confidence: 99%
“…It has been reported that 75 percent of the total renin activity is active renin in the rat ovary [38], suggesting that there is a tissue specificity in the processing rate from prorenin to renin. In summary, this is the first case report of renin producing leiomyosarcoma derived from the lung, and is characterized by relatively lower plasma prorenin concentrations.…”
Section: Discussionmentioning
confidence: 99%